Planting churches cross-culturally : a guide for home and foreign missions - Hesselgrave, David J.; Blomberg, Earl J. (Grand Rapids, Mich. : Baker Book House, 1975)
This practical and biblical volume offers serious students and practitioners of mission a step-by-step approach to developing a master plan for entering a new community with a church planting program. Each aspect of the master plan is developed theologically, scientifically, and practically. Cultural differences are analyzed, and missionaries are guided in how to transcend their own cultural background. In biblical terms, the Christian mission is explained in a way that places evangelism and church planting and growth at the heart. Responsibilities of church leaders are clarified -- how to devise strategies and deploy resources to enter new areas, convert people, and organize churches. The framework for these church planting activities is the Pauline Cycle. - Back cover.
00 |tThe heart of the Christian mission --|tMethod and mission --|tEducation for mission --|tLeading the mission --|tSelecting target areas --|tDeploying the resources -- |tMeasuring growth --|tThe missionaries commissioned -- |tThe audience contacted --|tThe Gospel communicated -- |tThe hearers converted --|tThe believers congregated -- tThe faith confirmed --|tThe leaders consecrated --|tThe believers commended --|tThe relationships continued -- |tThe sending church convened --|gBibliography.
Includes bibliographical references and indexes.
Keywords: Church development, New; Church growth; Missions; Evangelistic work